The Effect of Fear of Missing Out (FoMO), Live Streaming, and Flash Sales on Impulse Buying of Fashion Products on Shopee Among Generation Z in Gresik - Rizka Maulidiyah; Elok Vilantika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study was conducted to examine the impact of Fear of Missing Out (FoMO), live streaming, and flash sale on impulsive purchasing behavior. behavior in purchasing fashion products on the Shopee platform by Generation Z in Gresik. A quantitative research approach was adopted in this study, with primary data collected via questionnaires distributed to Generation Z respondents residing in Gresik who had experience purchasing fashion products on Shopee. A purposive sampling method within a non-probability sampling framework was applied in this research. Sample size determination was conducted based on the total of 14 research indicators, multiplied by a factor of 10, resulting in 140 respondents used as the research sample. The analysis results reveal that Fear of Missing Out (FoMO) and flash sales have a positive and significant Effect on impulsive purchasing behavior, while live streaming demonstrates a favorable influence that is, however, not significant. These findings indicate that psychological factors and time-limited promotional strategies play a significant role in driving impulsive buying behavior among Generation Z, while the live streaming feature has not yet fully become a major factor in triggering spontaneous purchasing decisions. This study is expected to contribute to the development of research on digital consumer behavior and serve as a basis for consideration.